2021
DOI: 10.1002/hep.31624
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Proton Density Fat Fraction Treatment Response Criteria in Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is one of leading causes of chronic liver disease in the United States(1). NASH can lead to cirrhosis, end stage liver disease and hepatocellular carcinoma and has become one of the leading indications for liver transplant in the United States(2). Reversal of NASH and improvement of NASH-related fibrosis is a major unmet need in the field of liver disease. Several therapies have shown promise in the treatment of NASH-related fibrosis but there are no food and drug administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The primary efficacy end point was change in liver fat by MRI-PDFF imaging at 12 weeks. 22,23 TVB-2640 treatment resulted in significant relative and absolute reductions of liver fat compared to placebo in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The primary efficacy end point was change in liver fat by MRI-PDFF imaging at 12 weeks. 22,23 TVB-2640 treatment resulted in significant relative and absolute reductions of liver fat compared to placebo in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 93%
“…Secondary outcomes included MRI-PDFF responder criteria assessment as defined by a relative reduction in MRI-PDFF of 30% given its association with histologic response. [21][22][23]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…114 The ability of MRI-PDFF to track change in liver steatosis has been evaluated as a secondary endpoint in clinical trials with paired liver biopsies. [172][173][174][175] These preliminary studies have shown that changes in MRI-PDFF values correlate well with changes in steatosis on liver biopsy. In addition, it has been suggested that MRI-PDFF could be more sensitive than liver biopsy to detect small changes in liver steatosis.…”
Section: Evaluation Of Treatment Response In Therapeutic Trialsmentioning
confidence: 84%
“…Meaningful responses are being classified as those demonstrating either (i) a resolution of steatohepatitis as defined by a ballooning score of 0 and an inflammation score of 0-1 and no worsening of liver fibrosis, (ii) improvement in liver fibrosis greater than or equal to one stage and no worsening of steatohepatitis, or (iii) both resolution of steatohepatitis and improvement in fibrosis (8), often expressed as a two-point change in the NAFLD activity score (NAS) with no worsening in fibrosis. Analysis of a trial of ezetimibe in NASH showed that PDFF could distinguish histological responders from non-responders (32), which was later characterized as a relative reduction of~30% liver fat corresponding to a two-point change in NAS (33,34). Equally, data on the ability of cT1 to measure changes in fibroinflammatory disease have recently been published (30,31).…”
Section: Introductionmentioning
confidence: 99%